Failure to Control Caries in an AIDS-Affected Individual: A Case Report - Karen A. Nedwick-Castro; Alexandre R. Vieira (Case Reports in Dentistry)
Many patients today are living longer with certain health issues like human immunodeficiency virus (HIV). These patients take numerous medications (HAART: highly active antiretroviral therapy) that cause xerostomia, which increases caries risk. There are particular challenges when treating HIV-positive patients with decreased immune systems, which can also accelerate the progression of periodontal disease. This paper discusses one such case that was followed from 2002 to 2010 at the University of Pittsburgh School of Dental Medicine, where an HIV patient lost all his teeth despite investing thousands of dollars. It is also common sense that just performing restorations to decayed teeth is not enough to control the disease, but recommending a personalized preventive maintenance program to the patient is a must.